Application of copyright law in libraries and archives in Nigeria (2016)
All over the world, the products of man's intellect are recognized and protected by the intellectual property law. The essence of the recognition and protection is to ensure that man's creativity and ingenuity are not unduly harnessed and exploited. A broad division of intellectual property law is the copyright law which protects, among others, literary) and artistic works. Like any other civilized country, Nigeria has a copyright law. Libraries and archives, being the main custodians of and the most prominent intermediaries between users and copyrighted works, it is essential that they should be abreast of copyright law in Nigeria. Unfortunately, not much exposition has been made on the application of copyright law in libraries and archives in Nigeria. This paper, therefore, takes a look at Nigeria's Copyright Act and interprets its provisions for libraries and archives in Nigeria. Making reference to the practice in other countries, particularly the developed world, as well as relevant statutory’ provisions, the paper defines the obligations of libraries and archives in the enforcement of copyright law. The paper concludes by emphasizing the need for information professionals to be abreast of legislations relating to information provision and to balance the interest of information resources users with that of copyright owners in order to protect intellectual property rights.